LOXL2 labels inflammation-associated myofibroblasts predicting kidney allograft dysfunction and fibrosis - Schütz, Paula; Hüchtmann, Birte; Van Marck, Veerle; Heitplatz, Barbara; Walter, Carolin; Rixen, Rebecca; Pavenstädt, Hermann; Reuter, Stefan; Buscher, Konrad (Frontiers in Immunology, 2026)
Progressive allograft fibrosis remains a major obstacle in kidney transplantation. Early identification of patients at high risk could be instrumental to improve outcomes. Here, we investigated Lysyl oxidase like 2 (LOXL2) as a biomarker for graft fibrosis and dysfunction. Using single-cell sequencing and imaging of transplant biopsies, we found that LOXL2 labeled an intertubular myofibroblast-like cell type with a smooth muscle actin (SMA)-negative, CD68-positive phenotype and high extracellular matrix activity. These cells were present in non-fibrotic and fibrotic regions using collagen 3 as a scaffold. Native kidneys also harbored LOXL2+ myofibroblasts, albeit at much lower levels. Following transplant surgery, LOXL2+ cells could rapidly emerge within days, particularly during episodes of rejection, where they associated with leukocyte aggregates. Elevated cell numbers were not irreversible as shown in follow-up biopsies. A retrospective analysis of 118 biopsies revealed a significant association with fibrosis, inflammation, and kidney function but not with other Banff parameters. Non-rejecting allografts displayed high variability in LOXL2+ cells, with high abundance serving as a long-term predictor of reduced allograft function. Our findings point to a new subset of inflammation-associated myofibroblasts that may be useful as a biomarker for early fibrogenesis.